2015
DOI: 10.4212/cjhp.v68i3.1455
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Beers Criteria to Alternate Level of Care Patients in Hospital Inpatient Units

Abstract: Background:The Beers criteria were developed to help in identifying potentially inappropriate medications (PIMs) for elderly patients. These medications are often associated with adverse events and limited effectiveness in older adults. Patients awaiting an alternate level of care (ALC patients) are those who no longer require acute care hospital services and are waiting for placement elsewhere. They are often elderly, have complex medication regimens, and are at high risk of adverse events. At the time of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
11
0
6
Order By: Relevance
“…The incidence rate of PIMs in our analysis was higher than that reported by earlier studies in other countries, which found that the incidence rate of PIMs ranged from 3.5% in France to 46% in Canada. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of PIMs in our analysis was higher than that reported by earlier studies in other countries, which found that the incidence rate of PIMs ranged from 3.5% in France to 46% in Canada. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Além destes fatores, a complexidade do local onde o estudo é realizado também influencia no resultado da prevalência, já que muitas vezes em hospitais o uso de MPIs se faz necessário em algumas situações, contrastando com a atenção primária. O uso dos MPIs varia muito entre os diversos países, já que os medicamentos disponíveis para prescrição são distintos, tendo resultados de prevalência de 25,5% a 98,2% [12][13][14][15][16] . Um estudo realizado em um hospital terciário no Brasil apresentou uma alta prevalência do uso dos MPIs, tendo 95,5% dos idosos com pelo menos um MPI prescrito de acordo com o Critério de Beer (versão 2012), sendo a metoclopramida, o ácido acetilsalicílico e o cetoprofeno os MPI mais prescritos 14 .…”
Section: Introductionunclassified
“…Some data suggests high, and potentially inappropriate use, ranging from 27-58% in hospitalized patients. (5)(6)(7)(8) When prescribed in acute care, these medications pose a number of risks including cognitive impairment, falls, fractures, and increased mortality. (9)(10)(11)(12)(13)(14) Furthermore, there is a lack of high quality evidence supporting the bene ts of pharmacologic therapy in hospitalized patients with a sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%